Cognitive vulnerability to mood deterioration in an exercise cessation paradigm - Evans, M.; Rohan, K. J.; Meyerhoff, J.; Norton, R. J.; Sibold, J. S. (Journal of Clinical Sport Psychology, 2024)
Mood deterioration in response to exercise cessation is well documented, but moderators of this effect remain unknown. This study tested the hypothesis that physically active individuals with higher levels of cognitive vulnerability (i.e., tendencies toward negative thought content and processes in response to stress or negative mood states) are at greater risk for increased anxiety and depressive symptoms when undergoing exercise cessation. Community adults meeting recommended physical activity guidelines (N = 36) participated in a 4-week prospective, longitudinal study with 2 weeks each of maintained exercise and exercise cessation. Cognitive vulnerability measures included dysfunctional attitudes, brooding rumination, and cognitive reactivity (i.e., change in dysfunctional attitudes over a dysphoric mood induction). Anxiety and depression symptoms increased during exercise cessation. Brooding emerged as a risk factor for increases in tension scores on the Profile of Mood States-Brief during exercise cessation. Future studies should explore brooding as a mediator (i.e., potential mechanism) of exercise-induced mood deterioration.